Role of a co-metal in bimetallic Ni-Pt catalyst for hydrogenation of m-dinitrobenzene to m-phenylenediamine - Telkar, M. M.; Nadgeri, J. M.; Rode, C. V.; Chaudhari, R. (Applied Catalysis A-General, 2005)
Bimetallic Ni-Pt catalysts supported on carbon were found to give very high turn over frequency numbers and almost complete selectivity to m-phenylenediamine in m-dinitrobenzene hydrogenation as compared to the monometallic nickel catalysts. The XRD and XPS characterization revealed that most of the nickel remains as Ni2+ in a monometallic catalyst while, the addition of platinum leads to the stabilization of Ni-0 state, in case of bimetallic catalysts. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Bimetallic catalyst; Catalytic hydrogenation; m-dinitrobenzene; m-phenylenediamine; Selective hydrogenation; turn over number; XPS and XRD of nickel

Au-Pt nanoparticles in amine functionalized MCM-41: catalytic evaluation in hydrogenation reactions - Joseph, Trissa; Kumar, K. Vijay; Ramaswamy, A. V.; Halligudi, Shivaraj B. (Catalysis Communications, 2007)
Nano-sized Au-Pt nanoparticles (Au-Pt-bi-MNPs) have been synthesized by the simultaneous reduction of HAuCl4 and HPtCl6 by NaBH4 inside the channels of amine functionalized Si-MCM-41 (NH2-Si-MCM-41) at ambient conditions. These materials were characterized using chemical analysis, UV-vis, XPS, XRD, FT-IR, Surface area and TEM analysis. The size of these alloyed nanoparticles (bi-MNPs) were found in the range of 2-4 nm. These nanoparticles were evaluated to study their catalytic activities towards hydrogenation of aromatic nitro compounds. The catalytic activity of the Au-Pt bi-MNPs was found to be superior to monometallic An nanoparticles. (c) 2006 Published by Elsevier B.V.
Keywords: amine-functionalized MCM-41; Au-Pt nanoparticles; Catalytic hydrogenation

Hydrogenation activity and selectivity behavior of supported palladium nanoparticles - Nadgeri, J. M.; Telkar, M. M.; Rode, C. V. (Catalysis Communications, 2008)
Enhancement in activity and selectivity of catalytic hydrogenation using supported nanosize palladium catalyst has been investigated. Pd/C catalyst prepared in the presence of polyvinyl pyrrolidone (PVP) as a stabilizer gave Pd particle size in a narrow range of 3-5 nm. While, evaluating for hydrogenation of 2-butyne-1,4-diol, the rate enhancement was found to be 10 times higher as compared to the conventional (bulk) Pd catalysts. A proper choice of stabilizer (PVP) giving small particle size as well as highly dispersed nature of nano particles were the major factors for such a dramatic enhancement of activity. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: butynediol; Catalytic hydrogenation; nanosize palladium; Selective hydrogenation; SEM-EDX analysis; size distribution; supported Pd nanoparticles

Pd-catalyzed one-pot chemoselective hydrogenation protocol for the preparation of carboxamides directly from azides - Bavikar, Sudhir N.; Salunke, Deepak B.; Hazra, Braja G.; Pore, Vandana S.; Thierry, Josiane; Dodd, Robert H. (Tetrahedron Letters, 2010)
Carboxamides were obtained efficiently in high yields from azides on reaction with the corresponding pre-formed activated carboxylic acids in a single-step reductive transformation using hydrogen atmosphere (balloon) under Pd/BaSO(4) or Pd/CaCO(3) catalysis. The method is highly chemoselective and compatible with extremely labile functional groups such as benzyl carbamates, benzyl ethers, benzyl esters, and olefins. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Azide; Carboxamide; Catalytic hydrogenation; Chemoselective; Palladium; Succinimide ester